Distance Education Students ' Perception of Online Learning during Covid-19 Era: A Study of Selected Campuses and Learning Centres of Valley View University - Ameyaw, Samuel (University of Dar es Salaam Library Journal, 2023)
The aim of this study is to determine distance education students ' perceptions of online learning during the COVID-19 era. The descriptive design was employed to examine students' views on online learning. The population of the study was 876 students from all the campuses and learning centres of Valley View University (VVU) across the country. The Yamane (1967) sample size calculation formula was used to sample the respondents. The questionnaire was the only data collection instrument used in this study. The researcher sent copies of the questionnaire to the participants via Google forms. The IBM- Statistical Product and Service Solutions (IBM-SPSS) was used for the analysis. The study found that the perceptions of the majority of the students toward online learning were negative. The results revealed that smartphones were ranked first with a value of (RII = 0.659) as the devices used by students during online learning classes. The findings indicated that students found it difficult to access internet services when they were at home, with a value of (RII= 0.644). The study concluded that these findings have the potential to assist University Management in addressing all issues confronting distance learning students. It is suggested that the University's Administration should work with the various telecommunication networks to provide distance learning students with free internet data while they are at home to enable them to fully participate in online learning classes.